Effect of Electroacupuncture at Shenting and Baihui Acupoints on Ability of Learning and Memory and Expression of Autophagy Related Genes and Proteins in Cerebral Ischemia-reperfusion Injuried Rats - Lingli GAO; Xiaodong FENG (康复学报)
Objective:To explore the mechanism of cognitive impairment treated by electroacupuncture (EA), and the expression of autophagy related genes and proteins in hippocampus of cerebral ischemia-reperfusion rats after EA at the shengting (DU24) and baihui (DU20) acupoints treament would be observed.Methods:A total of 48 SD male rats of clean grade were randomly divided into the EA group (n=18), the model group (n=18) and the sham operation group (n=12). The improved Zea Longa line embolism method was used to establish a model of ischemia and reperfusion injury in rats, EA was applied for 30 minutes each time, one time per day until the rats were sacrificed after ten days. Morris water maze experiment was used to observe learning and memory ability of rats, TTC staining was used to observe the change of brain infarction area of rats, RT-PCR and Western Blot were used to detect the expression of autophagy related genes and proteins in hippocampus.Results:④Morris water maze outcomes showed that compared with the model group, the escape latency time of rats in the EA group was obviously shortened, the number of across-platform was increased and the distance was shortened (P<0.05).④Compared with the model group, the nerve defect scale of brain ischemia-reperfusion injury rats in the EA group was decreased (P<0.05).④TTC staining results showed that the area of brain infarction in the EA group and model group was respectively higher than that in the sham operation group, and the volume of brain infarction in the EA group was reduced compared with the model group (P<0.05).④Compared with the model group, the levels of Beclin 1, LC3Ⅰ/Ⅱand PI3K mRNA and protein in the left side of hippocampus in the EA group were increased (P<0.05).Conclusion:EA at the DU24 and DU20 acupoints can reduce the cerebral infarction, and improve animal behaviors, and protect the neuronal injury. Regulation of autophagy network system may be one of the biologic mechanisms of EA improving cognitive impairment after stroke.